A Comparative Study of Secondary Procedures after Subpectoral and Prepectoral Single-Stage Implant-Based Breast Reconstruction. Issue 1 (4th October 2022) - Abbas, Abeera; Rizki, Hirah; Tanska, Aleksandra; Concepcion, Mae; Tasoulis, Marios Konstantinos; Gui, Gerald
Abstract : Background: Implant-based breast reconstruction (IBR) is the most commonly used procedure to reconstruct the breast after mastectomy. The advantages and disadvantages of subpectoral versus prepectoral implant placement remain a matter of debate. This study compares the need for secondary aesthetic procedures between prepectoral and subpectoral IBR. Methods: This is a retrospective cohort study of consecutive patients who underwent subpectoral or prepectoral IBR between 2015 and 2018 under a single surgeon at a tertiary breast unit. The primary endpoint was the number of secondary procedures performed to improve the aesthetic outcome. Secondary endpoints included the number of secondary procedures during the first year. Results: A total of 271 one-stage IBRs were performed (subpectoral, n = 128 in 74 patients; prepectoral, n = 143 in 84 patients). Overall, more patients required secondary procedures in the subpectoral group (36.5% versus 19%; P = 0.014), although through longer follow-up. The most common procedures were pocket revision and implant exchange [11.7% versus 3.5% ( P = 0.010); 11.7% versus 4.2% ( P = 0.021)], whereas fat grafting was similar between the two groups (46% versus 40.5%; P = 0.777). When adjusted for follow-up time, there was no significant difference in the number of secondary procedures undertaken in the subpectoral versus the prepectoral group (21% versus 16%, respectively; P = 0.288) at 1 year. Conclusions: The requirement for secondary procedures at 1 year was not different between groups. The need for fat grafting was not increased following prepectoral IBR. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.